Validation of the HPLC-UV Method for Quantitative Determination of Steroid Sapogenin Diosgenin from Hay Fenugreek Seeds, Trigonella Foenum-graecum L. - A. E. Sukhanov; A. N. Stavrianidi; E. D. Kubasova; A. S. Panasyuk; O. V. Buyuklinskaya (Разработка и регистрация лекарственных средств)
Introduction. Modern pharmacognostic research is aimed at searching for plant biologically active individual compounds (hereinafter referred to as RBAIS) isolated from plant extracts.Aim. Validation of HPLC-UV quantitative determination of sapogenin diosgenin in plant extracts from fenugreek seeds.Materials and methods. The object of study was raw materials-fenugreek seeds produced as medicinal plant raw materials by LLC «Sage» (Irkutsk). Validation of the method was carried out according to the parameters: specificity, linearity, correctness, precision in accordance with the requirements of SP XIV. One series of medicinal plant raw materials was used for the analysis, such as serial number – 010117, release date – 15 february 2017.Results and discussion. Validation characteristics were determined and their compliance with the necessary acceptance criteria was experimentally confirmed.Conclusion. It is established that the developed method of identification and quantitative determination of diosgenin in fenugreek seed extracts by HPLC-UV is correct, precise, specific and linear in the analytical field.